292 Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) in patients with advanced ovarian, fallopian tube or primary peritoneal cancer: our experience in 108 patients. (18th September 2019) - Capilna, ME; Moldovan, B; Rad, C; Moldovan, AA; Cozlea, AL; Fandi, A; Gheorghe, M; Kiss, SL
Abstract : Objectives: Current evidence suggests that complete cytoreductive surgery (CRS) and hypertermic intraperitoneal chemotherapy (HIPEC) is a feasible option for patients with advanced ovarian, fallopian tube or primary peritoneal cancer with potential benefits that may exceed the survival outcomes of current - surgical debulking and intravenous platinum- and taxane-based chemotherapy. Methods: It is a retrospective study including 108 patients with primary or recurrent peritoneal carcinomatosis, operated between 2013 and 2019, with a mean age of 53.7 years. Results: Seventy eight patients (72%) had primary debulking and 30 (27%) had surgery for a recurrent disease. The peritoneal cancer index (PCI) was below 15 in 50 patients (46%) and above 15 in 58 (53%), respectively. Together with total peritonectomy, large bowel resection was performed in 55 patients (50.9%), small bowel resection in 13 (12%), and splenectomy in 38 (35%). Other upper abdominal procedures included liver resection (13%), colecistectomy (35%), gastric resection (1.8%), diaphragm resection (12%), etc. Microscopically complete cytoreduction (CC0) was achieved for 68 patients (63%), macroscopic cytoreduction (CC1) for 35 (32%), and gross tumour debulking (CC2) for 5 (4%). Only 3 patients (2.7%) have been reoperated. For HIPEC, Cisplatin and respectively, Doxorubicin were both used for 30 patients (27%), Other regimen included Cisplatin plus Doxorubicin (41%), Cisplatin plus Mitomicine or Mitomicine alone. Nine patients (8%) died of disease, 15 (13%) are alive with reccurent disease, and 84 (77%) are disease-free, but the follow-up is short. Conclusions: HIPEC after extensive CRS for advanced gynecological cancer with peritoneal carcinomatosis is a feasible option with promising results.